Stressful life events among patients with dissociative and somatoform disorder - Tabassum, R; Haque, M; Chowdhury, SH (Journal of Armed Forces Medical College, Bangladesh, 2013)
DOI: http://dx.doi.org/10.3329/jafmc.v8i1.13532 JAFMC Vol.8(1) 2012 pp.09-14